PSYCHOLOGICAL MECHANISMS OF THE ORIGIN OF STUMMING IN PRESCHOOL CHILDREN (Psychology Travelogs, 2025)
The article presents one of the speech disorders of preschool children, namely stuttering, reveals the history of its development and causes of occurrence. It is emphasized that stuttering is a polymorphic speech disorder, a communication disorder in the form of dyscoordination of fluency, rhythm, the occurrence of individual stuttering, repetitions of a number of sounds and syllables as a result of speech convulsions due to overstrain or stress. It is emphasized that the most numerous categories in which this speech defect is observed is often children who are prone to anxiety. In particular, children who often witness various family conflicts in which increased convulsive activity is observed; children with delayed speech development; children whose parents are too strict in their upbringing; children who are overloaded due to spending a significant amount of time on gadgets and in front of the TV. It is specified that awareness of the causes of stuttering in humans, timely diagnosis and receiving qualified help helps to eliminate this speech disorder and improves human life. Scientific approaches, in particular, competency-based, systemic-structural, communicative, integrative, to the study of the specified phenomenon are analyzed. It is emphasized that most of the researchers pay attention to the complex approach, which consists of treatment (therapeutic, surgical, orthopedic, psychotherapeutic), upbringing and education, which complement each other. The symptoms of stuttering and its psychological mechanisms are determined (psycho-emotional tension, self-doubt, fear of speech, conflict between the desire to express oneself and the fear of not being understood by others, authoritarian upbringing style, etc.). The reasons that determine the symptoms of stuttering are characterized.
Keywords: stuttering; psychological mechanisms; logoneurosis; neurotic form; neurosis-like form; spasmophilia; logophobia; spasmodic contractions; correction techniques